PENGARUH PENDIDIKAN KESEHATAN TENTANG PEMERIKSAAN PAYUDARA SENDIRI (SADARI) TERHADAP PENGETAHUAN REMAJA PUTRI KELAS VII SMP NEGERI 2 KARTASURA - Popy Astriani; Shinta Rositasari; Anik Suwarni (Jurnal Ilmu Keperawatan Indonesia (JIKI), 2020)
Background: A lot of people with breast cancer have been found at a teenager. Even, there are many girl on fourteen-year-old has a tumor in her breast and it can potentiallybecome cancer if it is not detected earlier. Self Breast Examination (Pemeriksaan Payudara Sendiri/ SADARI) is an effective way to detect the presence of a lump in the breast early. Therefore, it can reduce the mortality rate by 25-30%. Preliminary study indicated that 13 female students who did know ans understand about Pemeriksaan Payudara Sendiri (SADARI) so student knowledge of Health Education on Pemeriksaan Payudara Sendiri (SADARI) should be improved. The aim of the study is to determine the effect of health education about Pemeriksaan Payudara Sendiri (SADARI) on the girl.Method: This research used Quasi Experimental. The population was 133 female students. Meanwhile, sample was taken based on Slovin formula and obtained 100 female students. The sampling techniques used proportional stratified random sampling and data analysis techniques used Paired Sample T-Test. Research Results: (1) The average of girl knowledge about Pemeriksaan Payudara Sendiri (SADARI) before health education was 17.54. (2) The average of girl knowledgeabout Pemeriksaan Payudara Sendiri (SADARI) after health education was 19.66. (3) There is an effect of health education about Pemeriksaan Payudara Sendiri (SADARI) to the girl knowledge ( p = 0,0001). Conclusion: There is an effect of health education about Pemeriksaan Payudara Sendiri (SADARI) to the girl knowledge